Regional ecological risk assessment of chemical industry stress under China's coastal development strategy. (15th November 2022) - Zhao, Haixia; Zhu, Tianyuan; Luo, Xinliao; Niu, Mingjie; Zhang, Lei; Gu, Binjie
Abstract: Governments and scholars are taking a closer look at risk assessment of areas developing chemical industries because of the repeated occurrence of chemical explosion accidents along coastal regions. The paper constructs an indicator system for Jiangsu Province based on three dimensions: risk source strength, receptor vulnerability, and risk prevention capability. It comprehensively evaluates the risks under stress from the chemical industry since the implementation of the coastland development strategy. The results show that a first rise in and then a decline in comprehensive risk along the coast of Jiangsu Province could be observed from 2007 to 2017. As a whole, the risk of contamination was dispersed, while locally, it accumulated and gradually shifted to areas along the river and adjacent coastal areas. High-risk areas are mainly distributed in chemical industry clusters. Risk sources continue to intensify with the increase in heavy chemical industry clusters. Generally, receptor vulnerability was high in the west, low in the east, high in the north and south, and low in the middle. The Tongyu River, Sheyang River, coastal wetlands, and canals in Nantong are among the most vulnerable areas. There is still a weak overall situation, with a pattern of 'high-low-high' staggered distribution from south to north, even though the risk prevention capacity is growing steadily.